Unlock Your Career Potential: Interactive Workshop on Job Interview Skills: Penelitian - Vivi Ayu Lestari; Ahmad Najib Mutawally; Arif Budimansyah Purba; Wafiqah Yasmin; Anwar Hilman; Wahyudi; Ludovikus (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In today's competitive job market, many students and recent graduates face significant challenges in securing employment, particularly when it comes to mastering interview skills. Research shows that a large percentage of job seekers feel unprepared for interviews, often struggling with communication and confidence. The rise of virtual interviews has further complicated this process, introducing new dynamics that candidates must navigate, such as technical issues and effective online presence.Additionally, employers increasingly use behavioral questions to assess candidates, which can leave many feeling uncertain about how to respond effectively. To address these challenges, we propose the